1981
DOI: 10.1148/radiology.141.1.7291544
|View full text |Cite
|
Sign up to set email alerts
|

Systemic embolization as a complication of transhepatic venography.

Abstract: Many patients with cirrhosis and portal hypertension demonstrate a right-to-left shunt, caused by development of anastomoses connecting the high-pressure periesophageal veins with the low-pressure bronchial and/or pulmonary veins at the level of the pulmonary hili. These anastomoses from the pathway by which small Gelfoam particles injected into the coronary or short gastric veins may embolize the systemic arterial circulation. Such embolization could have serious consequences, but reports of such complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In addition, cyanoacrylate injection also carries a risk of pulmonary embolization, multiple systemic embolization such as splenic infarction, and cerebral infarction, all of which rarely occur but can be fatal (27-30). Such complications may be related to major shunt or porto-pulmonary venous anastomosis (PPVA) (31,32), which flow into the pulmonary vein.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cyanoacrylate injection also carries a risk of pulmonary embolization, multiple systemic embolization such as splenic infarction, and cerebral infarction, all of which rarely occur but can be fatal (27-30). Such complications may be related to major shunt or porto-pulmonary venous anastomosis (PPVA) (31,32), which flow into the pulmonary vein.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PPVA is a potentially dangerous channel that can result in systemic arterial embolism. Ellman et al reported two cases in which particles of Gelfoam used to embolize the coronary and short gastric veins passed into the systemic arterial circulation through a portopulmonary anastomosis and embolized in the brain, spleen and heart (2).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other portosystemic pathways in portal hypertension patients, PPVA leads to a right-to-left shunt and thus has clinical implications dissimilar to those of a portosystemic shunt. The reported complications of a portopulmonary shunt via PPVA include cardiac failure and systemic arterial embolism (1,2). Therefore, radiologists should be aware of this unusual collateral pathway.…”
mentioning
confidence: 99%
“…Four case series in the Table [3,[8][9][10] were prompted by reports of systemic embolization associated with needle or catheter techniques used to treat or prevent bleeding from gastroesophageal varices [19]. The authors hypothesized that occult PPVA could increase the risk of systemic embolization as a complication of treating gastroesophageal varices with sclerosing, thrombosing, or occluding materials.…”
Section: Among Patients With Advanced Cirrhosis What Is the Frequencmentioning
confidence: 99%
“…Miura et al [3] reviewed evidence for systemic embolization associated with endoscopic sclerotherapy for gastroesophageal varices with cyanoacrylate and percutaneous transhepatic obliteration of gastroesophageal varices with gel foam. Ellman et al [19] reported two cases in which particles of gel foam used to embolize the coronary and short gastric veins passed into the systemic arterial circulation, presumably through a PPVA. Embolization to the brain, spleen and heart occurred.…”
Section: Among Patients With Advanced Cirrhosis What Is the Frequencmentioning
confidence: 99%